A population‐based survey of risk for cancer in individuals diagnosed with myotonic dystrophy. Issue 4 (7th July 2016) - Abbott, Diana; Johnson, Nicholas E.; Cannon‐Albright, Lisa A.
ABSTRACT: Introduction : The risk of cancer in patients diagnosed with myotonic dystrophy (DM) is reported for the homogeneous Utah population. Methods : Clinical data accessed from the largest Utah healthcare providers have been record‐linked to the Utah Population Database, a population‐based resource also linked to the Utah Cancer Registry. Relative risks were estimated for 36 cancers of different types in 281 DM patients. Results : Testicular cancer (relative risk [RR] = 10.74; 95% confidence interval [CI], 1.91–38.79), endometrial cancer (RR = 6.98; 95% CI, 1.24–25.22), and non‐Hodgkin lymphoma (RR = 4.25; 95% CI, 1.16–12.43) were all observed at significant excess in DM patients. Conclusions : This study confirms an overall increased risk of cancer in DM. Individuals diagnosed with DM might benefit from risk counseling. Muscle Nerve 54 : 783–785, 2016